2006
DOI: 10.1128/mcb.26.7.2782-2790.2006
|View full text |Cite
|
Sign up to set email alerts
|

Acetylation of p53 at Lysine 373/382 by the Histone Deacetylase Inhibitor Depsipeptide Induces Expression of p21Waf1/Cip1

Abstract: Generally, histone deacetylase (HDAC) inhibitor-induced p21Waf1/Cip1 expression is thought to be p53 independent. Here we found that an inhibitor of HDAC, depsipeptide (FR901228), but not trichostatin A (TSA), induces p21 Waf1/Cip1 expression through both p53 and Sp1/Sp3 pathways in A549 cells (which retain wild-type p53). This is demonstrated by measuring relative luciferase activities of p21 promoter constructs with p53 or Sp1 binding site mutagenesis and was further confirmed by transfection of wild-type p5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
213
1
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 266 publications
(234 citation statements)
references
References 74 publications
(127 reference statements)
17
213
1
3
Order By: Relevance
“…HDAC4 represses p21 WAF1/Cip1 in cancer cells in vitro in a Sp1-dependent manner Although most reports demonstrated that HDAC inhibitors induced p21 WAF1/Cip1 expression in an Sp1/Sp3-dependent manner Sowa et al, 1997Sowa et al, , 1999Han et al, 2001;Wilson et al, 2006), a role for p53 in HDAC-associated p21 WAF1/Cip1 expression has also been reported in several human cancer cell lines (Lagger et al, 2003;Luo et al, 2004;Roy et al, 2005;Zhao et al, 2006).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…HDAC4 represses p21 WAF1/Cip1 in cancer cells in vitro in a Sp1-dependent manner Although most reports demonstrated that HDAC inhibitors induced p21 WAF1/Cip1 expression in an Sp1/Sp3-dependent manner Sowa et al, 1997Sowa et al, , 1999Han et al, 2001;Wilson et al, 2006), a role for p53 in HDAC-associated p21 WAF1/Cip1 expression has also been reported in several human cancer cell lines (Lagger et al, 2003;Luo et al, 2004;Roy et al, 2005;Zhao et al, 2006).…”
Section: Resultsmentioning
confidence: 96%
“…To date, the most common model for p21 WAF1/Cip1 repression in cancer cells is the recruitment of HDACs by Sp1/-Sp3 transcription factors in the proximal promoter region encompassing the Sp1/Sp3 binding sites, which in turn repress p21 WAF1/Cip1 transcription by deacetylating histones H3 and H4. However, a role for p53 in HDAC-associated p21 WAF1/Cip1 expression has also been reported in several human cancer cell lines (Lagger et al, 2003;Luo et al, 2004;Roy et al, 2005;Zhao et al, 2006).…”
Section: Introductionmentioning
confidence: 97%
“…p53 acetylation is removed by HDACs. HDAC1 has been shown to deacetylate p53 at Lys 373/382 to induce p21 expression (Zhao et al 2006). p21 can also be activated by HDACis through p53-independent pathways (Gartel and Tyner 1999;Ocker and Schneider-Stock 2007).…”
Section: Resultsmentioning
confidence: 99%
“…The 18 human HDACs may be classified as either zinc-or NAD 1 -dependent and further subclassified into class I (HDAC1, 2, 3, and 8), class II (HDAC4, 5, 6, 7, 9, and 10), class III (including NAD 1 -dependent sirtuins), and class IV (HDAC11) HDACs. As HDACs regulate a wide variety of processes involved in carcinogenesis, multiple mechanisms may explain the clinical activity of HDAC inhibitors [249,250], including altered gene expression of cell-cycle and apoptotic regulatory proteins [251][252][253][254][255], acetylation of nonhistone proteins regulating cell growth and survival [256][257][258][259], angiogenesis [260,261], aggresome formation [262], and DNA repair [263]. In addition, HDAC inhibitors may have important effects on the tumor microenvironment via reactive oxygen species [264,265], enhanced antigen presentation [266] and downregulation of immunomodulatory cytokines, like IL-10 [267].…”
Section: Hdac Inhibitorsmentioning
confidence: 99%